2021
DOI: 10.3390/nu13062112
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Prebiotics, and Synbiotics: Implications and Beneficial Effects against Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is still a common functional gastrointestinal disease that presents chronic abdominal symptoms but with a pathophysiology that is not yet fully elucidated. Moreover, the use of the synergistic combination of prebiotics and probiotics, known as synbiotics, for IBS therapy is still in the early stages. Advancements in technology led to determining the important role played by probiotics in IBS, whereas the present paper focuses on the detailed review of the various pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 201 publications
0
84
0
8
Order By: Relevance
“…Furthermore, prebiotics and probiotics could be combined into "synbiotics" [23], so synergetic effects could be obtained, as the probiotic strain might be stimulated to grow by fermenting the prebiotic [6,24]. As of January 2022, there were 277 registered clinical trials (https://clinicaltrials.gov/ct2/results?term=prebiotics&Search=Apply&recrs= e&age_v=&gndr=&type=&rslt=, accessed on 6 January 2022) worldwide, the majority in Europe, which evaluated the effect of prebiotics (alone or in combination with probiotics) on body weight and obesity metabolic syndrome, type 2 diabetes mellitus, gastrointestinal disorders (diarrhea, constipation, enterocolitis), irritable bowel syndrome and inflammatory bowel disease, and cardiovascular diseases but also on anxiety disorders, arthritis, or allergies [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prebiotics and probiotics could be combined into "synbiotics" [23], so synergetic effects could be obtained, as the probiotic strain might be stimulated to grow by fermenting the prebiotic [6,24]. As of January 2022, there were 277 registered clinical trials (https://clinicaltrials.gov/ct2/results?term=prebiotics&Search=Apply&recrs= e&age_v=&gndr=&type=&rslt=, accessed on 6 January 2022) worldwide, the majority in Europe, which evaluated the effect of prebiotics (alone or in combination with probiotics) on body weight and obesity metabolic syndrome, type 2 diabetes mellitus, gastrointestinal disorders (diarrhea, constipation, enterocolitis), irritable bowel syndrome and inflammatory bowel disease, and cardiovascular diseases but also on anxiety disorders, arthritis, or allergies [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a beneficial anti-inflammatory effect has also been observed in certain pathological situations [ 78 ]. The mechanisms involved in these beneficial effects are currently the subject of numerous studies [ 84 ]. In addition, the neutrophil/lymphocyte ratio is a marker that reflects the state of systemic inflammation or oxidative stress [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous diseases including Coronavirus Disease (COVID-19), Irritable Bowel Syndrome (IBD), and kidney disease, which are associated with gastrointestinal disorders, have found that the disruption of gut bacteria may play an important role ( 57 , 58 ). Probiotic strains significantly activate the aromatic hydrocarbon receptor (AhR) way to stimulate the intestinal immune system to relieve GI symptoms ( 59 ). Dimidi et al ( 60 ) revealed that administration of probiotics decreased gut transit time, increased stool frequency, and improved some constipation-related symptoms.…”
Section: Discussionmentioning
confidence: 99%